Phylogeography Study Of The Indigenous People Of Sabah: Kadazan, Dusun, Rungus And Bajau - Gan, Yee Min (2020)
Phylogeography is a field of study that applies phylogenetic research in the field of archaeology to study past human migration and settlement patterns. In Southeast Asia (SEA), it has been extensively used to study the Austronesian diaspora, possibly the most widespread movement of a single ethnolinguistic group. Through archaeological and linguistic evidence, it has been shown that rice farmers who were proto-Austronesian speakers migrated from South China into Taiwan c. 5,500 years ago. Austronesian languages then developed in Taiwan and Austronesian speakers subsequently spread into SEA, Oceania and Polynesia c. 4,000 years ago. This movement has been coined as the “Out of Taiwan” dispersal. However, recent genetic studies show that the situation is much more complex than this. Some scholars suggested multiple dispersals rather than a one-off migration, as well as a back or reverse migration into Taiwan instead of one that is mono-directional. In Sabah (Borneo, Malaysia), all the indigenous ethnic groups speak Austronesian languages such as the Dusunic and Sama-Bajau languages; this marks an invasion, acculturation or assimilation of Austronesian speakers in the region. However, Sabah has not been subjected to much phylogenetic analysis as compared to neighbouring regions such as the Philippines and Indonesia in spite of its strategic location. Hence, this study aims to fill this research gap by conducting a phylogenetic analysis using the maternally inherited mitochondrial DNA (mtDNA) on four major Sabah ethnic groups, namely the Kadazan, Dusun, Bajau and Rungus.